Investigating English as Lingua Franca in the Indonesian multilingual context: Perceptions of English learners at the university level - Wulandari Santoso; Ronald Maraden Parlindungan Silalahi; Bertaria Sohnata Hutauruk (International Journal of English Linguistics, Literature, and Education (IJELLE), 2023)
The phenomenon of English as Lingua Franca (ELF) in Indonesia's multilingual pedagogical context is fascinating to study because the linguistic ecology in Indonesia is multilingual and multicultural. ELF reflects the spirit of learning open to various linguistic variations and focuses on the ability to communicate in diverse sociocultural contexts. The ideology of ELF in English Language Teaching (ELT) can be seen from the openness to use various variations of English outside of the native to be applied in the classroom to build cross-cultural communication competence. This study aims to analyze the perceptions of English learners (English Department) towards ELF and to find its relevance for future learning development. This research is quantitative-qualitative (Mixed-Method) with 130 English department student respondents from several campuses in Indonesia. Triangulation was carried out with seven students with different specializations (Linguistics, Literature, translation, and teaching). This research clearly shows the rejection of ELF in Indonesia's learning context and emphasizes the influence of native speakerism ideology. Even so, it is hoped that this research can still be developed in other studies in the future because multilingual pedagogical contexts are very diverse and can be seen from various perspectives.